The epidemiology of subclinical malaria infections in South-East Asia: findings from cross-sectional surveys in Thailand-Myanmar border areas, Cambodia, and Vietnam - Imwong, M; Nguyen, T; Tripura, R; Peto, T; Lee, S; Lwin, K; Suangkanarat, P; Jeeyapant, A; Vihokhern, B; Wongsaen, K; Van Hue, D; Dong, LT; et al. (BioMed Central, 2015)
Backround The importance of the submicroscopic reservoir of Plasmodium infections for malaria elimination depends on its size, which is generally considered small in low transmission settings. The precise estimation of this reservoir requires more sensitive parasite detection methods. The prevalence of asymptomatic, sub-microscopic malaria was assessed by a sensitive, high blood volume quantitative real-time polymerase chain reaction method in three countries of the Greater Mekong Sub-region. Methods Cross-sectional surveys were conducted in three villages in western Cambodia, four villages along the Thailand-Myanmar border and four villages in southwest Vietnam. Malaria parasitaemia was assessed by Plasmodium falciparum/pan malaria rapid diagnostic tests (RDTs), microscopy and a high volume ultra-sensitive real-time polymerase chain reaction (HVUSqPCR: limit of detection 22 parasites/mL). All villagers older than 6 months were invited to participate. Results A census before the surveys identified 7355 residents in the study villages. Parasite prevalence was 224/5008 (4 %) by RDT, 229/5111 (5 %) by microscopy, and 988/4975 (20 %) when assessed by HVUSqPCR. Of these 164 (3 %) were infected with P. falciparum, 357 (7 %) with Plasmodium vivax, 56 (1 %) with a mixed infection, and 411 (8 %) had parasite densities that were too low for species identification. A history of fever, male sex, and age of 15 years or older were independently associated with parasitaemia in a multivariate regression model stratified by site. Conclusion Light microscopy and RDTs identified only a quarter of all parasitaemic participants. The asymptomatic Plasmodium reservoir is considerable, even in low transmission settings. Novel strategies are needed to eliminate this previously under recognized reservoir of malaria transmission.